Answer:
Following are the answer to this question:
Step-by-step explanation:
In option 1:
The value of n is= 7, which is (base case)
![\to 3^7<7!\\\to 2187<5050\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/b4fv2fp35me9dziyf4xoyqvk5gl7zdteow.png)
when n=k for the true condition:
![\to 3^k<k!......(i)\\\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/5zxfma0lratzwsay1odrt0w30ebm0qjkqc.png)
when n=k+1 it tests the value:
![\to 3^((k+1))= 3^k,3\\\to < (k!) 3 \ substituting \ equation \\\to <k! \cdot (k+1)\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/q47mjn22hkwdumbajkmnqhznpdtoo7yt4z.png)
since k>6 hence the value is KH>3 hence proved.
In option 2:
when:
for n=1:(base case)
![\log(1!)<=1\log(1)](https://img.qammunity.org/2021/formulas/computers-and-technology/college/s35shpsfcnibiflaf60lozsoqhqntx1cs1.png)
0<=0 \\ condition is true
when the above statement holds value n=1
when n=k
![\log(k!) <=k\log(k)....(1)](https://img.qammunity.org/2021/formulas/computers-and-technology/college/kb1o3bhol5aq2n8oblqo6jqb4pby2xddku.png)
when n=k+1
![\log(k+1)!=\log(k!)+\log(k+1)\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/7lq5vb3zllzxvl32c6i5tdwxpsb3lf7d78.png)
![<= k \log(k)+\log(kH)\\<= kH\log(kH)\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/7pjgokgz228nwu83hnhr1pc5gnhzo6tkv5.png)
![[\therefore KH>K \Rightarrow \log(KH>\loK)]](https://img.qammunity.org/2021/formulas/computers-and-technology/college/b4m8f5guqk1y2p6momfa0wk1rbjkos54om.png)
In option 3:
when n=1:
![A_1 \cup B=A_1 \cup B\\\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/pmjsftuwn93323wqbzq96b0xh8pfr7z5wu.png)
when n=k
![\to (A_1\cap A_2 \cap.....A_k) \cup B\\=(A_1\cup B) \cap(A_2\cup B_2)....(A_k \capB).....(a)\\\to n= k+1\\ \to (A_1\cap A_2 \cap.....A_(kH)) \cup B= (A_1\cup B)\\\\\to [(A_1\cap A_2 \cap.....A_(k)) \cup B]\cap (A_(KH)\cup B)\\\\\to [(A_1\cup B) \cap (A_2 \cup B) \cap (A_3\cup B).....(A_k\cup B)\cap (A_(k+1) \cup B)\\\\ \ \ \ \ \ \ substituting \ equation \ a \\\\](https://img.qammunity.org/2021/formulas/computers-and-technology/college/bj4qbd1mjz6tp90qnj0rf0rouoifrgvdy9.png)
hence n=k+1 is true.